1130 Clinical features and clinical course of sporadic inclusion body myositis (IBM): a prospective cohort study: IBM-net. Issue 3 (9th February 2012) - Cortese, A; Machado, P; Miller, A; Brady, S; Hilton-Jones, D; Morrow, J; Hiscock, A; Dewar, E; Parton, M; Hanna, M
Abstract : Objective: To assess the clinical features and clinical course of sporadic Inclusion body myositis (sIBM) in a prospective cohort of patients diagnosed with definite or probable sIBM, according to Griggs criteria. Methods: Clinical data, muscle testing, myometry and IBM functional rating scale (FRS) were collected according to a standardised protocol (IBM-Net) at baseline (n=42) and 1-year follow-up (n=13). Results: The male:female ratio was 2:1, mean age at examination was 68 years (range 60–95) and at disease onset 58 (37–91). The mean latency between symptom onset and IBM diagnosis was 4.5 years. Only 30% of patients were initially referred for suspected sIBM, the other 70% had various initial suspected diagnoses including polymyositis, statin myopathy, ALS and peripheral neuropathy. Proximal asymmetrical weakness of lower limbs and grip weakness were the most common reported symptoms at onset. Falls represented the initial complaint in 20% of patients. Mean FRS at baseline was 27/40 (range 15–38). We found a high frequency of dysphagia, with 50% of subjects complaining of swallowing difficulties. The clinical evaluation and myometry consistently showed that finger flexors, knee extensors and foot dorsiflexors were the most severely affected muscles. A subgroup of 13 patients had a second evaluation after 1 year, showing a mean loss of muscle strength of 4.0% (p value=0.142) and a mean reduction in IBM-FRS of 14% (p value=0.005). Conclusions: This study describes one of the largest cohorts of IBM patients reported so far, providing crucial information to correctly define the features and natural history of sIBM and to adequately design future clinical trials.